Microstructure evolution and formation mechanism of CoCrCu1.2FeNi high entropy alloy during the whole process of semi‐solid billet preparation. (1st September 2022) - Jiang, Jufu; Huang, Minjie; Wang, Ying; Liu, Yingze; Zhang, Ying
Highlights: Coarsening kinetic equation describing solid grain growth was established. Segregation in FCC1 phase reduced and the lattice constant difference between the two phases decreased after isothermal heat treatment. During heating up, FCC1 and FCC2 phase recrystallized successively, FCC2 phase was spheroidized to a certain extent. FCC2 grains coalesced, grew up and spheroidized and the preferred orientations basically disappeared as heated to semi-solid range. Abstract: Dual face-centered cubic (FCC) CoCrCu1.2 FeNi semi-solid billets were prepared by semisolid isothermal treatment of wrought high entropy alloy (HEA) (SSITWH) method, and the microstructure evolution in the whole process of billets preparation was systematically investigated by optical microscopy, scanning electron microscopy, electron backscatter diffraction and transmission electron microscopy. The hot deformed feedstock was mainly composed of deformation structure with preferred orientations and a small number of dynamically recrystallized grains of FCC1 phase. In the semi-solid stage, the effect of temperature and soaking time on semi-solid microstructure was studied in the range of 1130–1250 °C and 5–120 min. The semi-solid microstructure was evaluated quantitatively. The average grain size and average shape factor increased with the increase of soaking time and isothermal temperature. After isothermal heat treatment, the segregation of Cu in FCC1 phase reduced to a certain extent. Semi-solid coarsening kinetics analysis showed that the alloy had low coarsening coefficients. When the temperatures were 1130 °C, 1175 °C, 1200 °C, 1225 °C and 1250 °C, the coarsening coefficients were 1.08 μm 3 /s, 5.95 μm 3 /s, 6.17 μm 3 /s, 17.58 μm 3 /s, 38.67 μm 3 /s, respectively. A coarsening kinetic equation describing solid grain growth was established. During heating up, FCC1 and FCC2 phase recrystallized successively. At higher temperature, FCC2 phase was spheroidized to a certain extent. When temperature was raised to semi-solid range, the grains of FCC2 phase coalesced, grew up and spheroidized and the preferred orientations basically disappeared. The types of semi-solid melting characteristics of HEAs were summarized in this paper. The semi-solid melting behavior of alloys is essentially affected by phase structure, phase number, phase volume content and composition.